Rivaroxaban versus nadroparin for preventing deep venous thrombosis after total hip arthroplasty following femoral neck fractures: A retrospective comparative study. Issue 5 (May 2018) - Zhang, Chi; Xu, Bo; Liang, Guanzhao; Zeng, Xianshang; Yang, Chen; Zhang, Fan; Wan, Zi; Yu, Weiguang; Chen, Deng; Ge, Zhe; Zhang, Xinchao
Objective: This study was performed to evaluate the efficacy of rivaroxaban versus nadroparin for preventing deep venous thrombosis (DVT) in elderly patients with osteoporosis undergoing initial total hip arthroplasty (THA) for femoral neck fractures. Methods: Prospectively maintained databases were reviewed to retrospectively compare elderly patients with osteoporosis who underwent initial THA for femoral neck fractures from 2007 to 2015. The patients received peroral rivaroxaban at 10 mg/day for 2 weeks or subcutaneous injections of nadroparin at 0.3 mL/day for 2 weeks until the primary analysis cut-off date. The time to first on-study DVT was the primary endpoint. Results: In total, 399 patients were included (rivaroxaban group: n=200; mean age, 70.20 ± 9.16 years and nadroparin group: n = 199; mean age, 69.90 ± 8.87 years), with a mean 3-year follow-up. The time to first on-study DVT was significantly longer in the rivaroxaban than nadroparin group (12 and 5 days, respectively). The incidence of DVT within the 2-week follow-up was significantly higher in the nadroparin than rivaroxaban group (6.8% and 19.7%, respectively), but this difference was no longer present at the final follow-up. Conclusion: Rivaroxaban was associated with a significant reduction in the occurrence of first on-study DVT compared with nadroparin.